1995
DOI: 10.1111/j.1479-828x.1995.tb01862.x
|View full text |Cite
|
Sign up to set email alerts
|

Fetomaternal Haemorrhage After External Cephalic Version at Term

Abstract: The incidence of fetomaternal haemorrhage after external cephalic version was 1.8% in 167 patients. The occurrence of this complication was not found to be associated with difficult or unsuccessful version, or with any adverse perinatal outcome. We conclude that routine assessment of fetomaternal haemorrhage after external version is not necessary, except in rhesus negative women to detect the 2% in whom the routine dose of 500 iu (100 micrograms) of anti-D immunoglobulin is inadequate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
3

Year Published

1999
1999
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 7 publications
0
10
0
3
Order By: Relevance
“…The largest bleed in their study was 117 cells/10,000 maternal cells, which corresponds to 6.5 ml of fetal red cells. Although Marcus et al [8] found an increase in the amount of FMH in cases with failed ECV, Tau et al [10] found no such association. Placental position has been related to success rates [3,6] and a posterior placenta is considered more favourable.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…The largest bleed in their study was 117 cells/10,000 maternal cells, which corresponds to 6.5 ml of fetal red cells. Although Marcus et al [8] found an increase in the amount of FMH in cases with failed ECV, Tau et al [10] found no such association. Placental position has been related to success rates [3,6] and a posterior placenta is considered more favourable.…”
Section: Discussionmentioning
confidence: 94%
“…Placental position has been related to success rates [3,6] and a posterior placenta is considered more favourable. Tau et al [10] did not find an anterior placenta to be a predisposing factor for FMH. In our case the placenta was anteriorly situated, but it would be difficult to conclusively implicate this as a cause for the massive FMH in view of the above contradictory reports.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations